12z+28-7z-3=

Simple and best practice solution for 12z+28-7z-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12z+28-7z-3= equation:


Simplifying
12z + 28 + -7z + -3 = 0

Reorder the terms:
28 + -3 + 12z + -7z = 0

Combine like terms: 28 + -3 = 25
25 + 12z + -7z = 0

Combine like terms: 12z + -7z = 5z
25 + 5z = 0

Solving
25 + 5z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + -25 + 5z = 0 + -25

Combine like terms: 25 + -25 = 0
0 + 5z = 0 + -25
5z = 0 + -25

Combine like terms: 0 + -25 = -25
5z = -25

Divide each side by '5'.
z = -5

Simplifying
z = -5

See similar equations:

| 6x+1=34-5x | | 32+(x-2)+32+(x-2)= | | 1.95y+6.834=7.65y-19.8591 | | 70=-7 | | 3*(x-31)=x-13 | | 5-4(6-3)= | | 13x-32=9x-4 | | 182=7(-5v-9) | | 7+8(3-9)= | | 13x+15=11x-2 | | (-3i)(8i)= | | 6-6x(9-9)/1/(2x6) | | 31/7=93/t | | -8•(7/2) | | -8•(-7/2) | | 9x-25=94 | | 14/9=42/t | | g(v)=3v+4 | | 28X=7X-14 | | 36=16t^2+48t | | 1/4x20/4 | | 12/16=42/x | | 28v^5x^2y^3-16v^9x^7= | | 3x+7+4(x)-2= | | IN(2x)=6 | | 8y=52 | | 63=r-45 | | 6/5-6v | | L-4/8=3 | | 8=5y+3 | | 6x^3-24x^2+40x-24=0 | | 3(5-3x)+6(5x-1)=0 |

Equations solver categories